Has the Basel II Accord Encouraged Risk Management During the 2008-09 Financial Crisis? - Michael McAleer; Juan-Angel Jimenez-Martin; Teodosio Pérez-Amaral (Tinbergen Institute, 2009)
The Basel II Accord requires that banks and other Authorized Deposit-taking Institutions (ADIs) communicate their daily risk forecasts to the appropriate monetary authorities at the beginning of each trading day, using one or more risk models to measure Value-at-Risk (VaR). The risk estimates of these models are used to determine capital requirements and associated capital costs of ADIs, depending in part on the number of previous violations, whereby realised losses exceed the estimated VaR. In this paper we define risk management in terms of choosing sensibly from a variety of risk models, discuss the selection of optimal risk models, consider combining alternative risk models, discuss the choice between a conservative and aggressive risk management strategy, and evaluate the effects of the Basel II Accord on risk management. We also examine how risk management strategies performed during the 2008-09 financial crisis, evaluate how the financial crisis affected risk management practices, forecasting VaR and daily capital charges, and discuss alternative policy recommendations, especially in light of the financial crisis. These issues are illustrated using Standard and Poor's 500 Index, with an emphasis on how risk management practices were monitored and encouraged by the Basel II Accord regulations during the financial crisis.
Keywords: G32; G11; G17; C53; C22; 330; Value-at-Risk (VaR); daily capital charges; exogenous and endogenous violations; violation penalties; optimizing strategy; risk forecasts; aggressive or conservative risk management strategies; Basel II Accord; financial crisis; Basler Akkord; Unternehmenspublizität; Bankenliquidität; Risikomaß; Risikomanagement; Finanzkrise